Theories of the Firm. Issue 1 (2nd January 2018) - Kay, John
Abstract: Since the seminal contributions of Coase, Williamson, Jensen and Meckling, and Easterbrook and Fischel, the characterisation of the firm as a nexus of contracts, its boundaries determined by the relative costs of markets and hierarchical organisation, has dominated the economic theory of the firm. The capabilities-based approach of Penrose, largely ignored by economists but developed in the resource-based theory of business strategy, provides a more illuminating perspective on a globalised and evolving business environment.